Análisis comparativo entre el motor jaula de ardilla y el motor de imán permanente para la eficiencia eléctrica en el pozo cuyabeno 68 como alternativa de levantamiento artificial para la extracción de crudo por bombeo electrosumergible. - Alomia Paredes, Jorge Leonardo (2019)
This research includes a comparative analysis of two engines such as the squirrel cage engine and the permanent magnet engine that could be implemented in an electrosubmersible pumping system as an artificial lifting alternative for crude oil extraction in Cuyabeno well 68, this research is performed because there is no research focused on the electrical efficiency of permanent magnet engine in this well, to carry out this research an electrosubmersible modeling pumping system was implemented for each engine using operational characteristics required by the well, this design was made by mathematical calculations, after finding the variables such as: pumping stages number were found; these were relatively compared with data obtained from a simulation software that serves only for the modeling of artificial lifting systems. The research continued to compare data each engine operational such as: speed, temperature, voltage, current and energy consumption of each machine, finally to develop an economic study to determine technical and economic feasibility to achieve the electrical efficiency in the electrosubmersible pumping system to determine the best option in Cuyabeno well 68 is the permanent magnet engine for its low consumption and energy cost.